Handbuch der altägyptischen medizin - Westendorf, Wolfhart. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1999)
Some 25 years ago the famous nine-volume Grundrisz der Medizin der alten Ägypter by Hildegard von Deines e.a. (editions.) saw the light. One of the editors was Professor Dr. Wolfhart Westendorf, the author of the new Handbuch der altägyptischen Medizin now published in Brill's series Handbook of Oriental Studies. At last the present handbook offers the readership an abridged and revised edition of the old Grundrisz . It deals with Ancient Egyptian Medicine from the second millennium up to the Roman period. In selecting the material for this volume the author based himself not only on the extant papyrus texts (both hieratic and demotic), but also on relevant passages from Egyptian literature like magical texts and ostraka and on archaeological evidence (mummies, represenations of patients). After an Introduction (science, religion, magic), there are chapters on sources, formal organisation of the underlying texts, patients and diseases, the physician (profession, social status, title, methods of treatment, dealing with drugs, using magic power, et cetera) on the end of Egyptian medicine in Coptic and Greek medicine, and the Ebers and Smith Papyri (with translations). The work concludes with extensive indices (places, themes, et cetera)